2015
DOI: 10.1111/ina.12218
|View full text |Cite
|
Sign up to set email alerts
|

Cooking‐related PM 2.5 and acrolein measured in grocery stores and comparison with other retail types

Abstract: We measured particulate matter (PM), acrolein, and other indoor air contaminants in eight visits to grocery stores in California. Retail stores of other types (hardware, furniture, and apparel) were also sampled on additional visits. Based on tracer gas decay data, most stores had adequate ventilation according to minimum ventilation rate standards. Grocery stores had significantly higher concentrations of acrolein, fine and ultrafine PM, compared to other retail stores, likely attributable to cooking. Indoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Source apportionment in this study attributed the residential VOC exposures to four source categories: “continuous indoor sources”, “outdoor origin”, “cooking”, and “other”. Time-resolved exposures and associated source apportionments are displayed in Figure for site H2 and subject H2M1 for the case of acrolein, an illustrative compound of health interest with prior evidence of both continuous indoor sources (lumber) and episodic sources (combustion and cooking). We note that acrolein has been previously measured in outdoor ambient air and retail stores near the H1 and H2 residences. , In the present study, daily occupant exposures to acrolein were mainly attributable to continuous indoor sources, with a median exposure of ∼4.6 ppb-hours per day (ppb-h d –1 ). Substantial variation was observed in daily exposures, principally due to variations in the fraction of time that occupants spent indoors combined with the effects of event-specific sources.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Source apportionment in this study attributed the residential VOC exposures to four source categories: “continuous indoor sources”, “outdoor origin”, “cooking”, and “other”. Time-resolved exposures and associated source apportionments are displayed in Figure for site H2 and subject H2M1 for the case of acrolein, an illustrative compound of health interest with prior evidence of both continuous indoor sources (lumber) and episodic sources (combustion and cooking). We note that acrolein has been previously measured in outdoor ambient air and retail stores near the H1 and H2 residences. , In the present study, daily occupant exposures to acrolein were mainly attributable to continuous indoor sources, with a median exposure of ∼4.6 ppb-hours per day (ppb-h d –1 ). Substantial variation was observed in daily exposures, principally due to variations in the fraction of time that occupants spent indoors combined with the effects of event-specific sources.…”
Section: Resultsmentioning
confidence: 51%
“…48−52 We note that acrolein has been previously measured in outdoor ambient air and retail stores near the H1 and H2 residences. 53,54 In the present study, daily occupant exposures to acrolein were mainly attributable to continuous indoor sources, with a median exposure of ∼4.6 ppb-hours per day (ppb-h d −1 ). Substantial variation was observed in daily exposures, principally due to variations in the fraction of time that occupants spent indoors combined with the effects of event-specific sources.…”
Section: Experimental Methodsmentioning
confidence: 60%
“…Chan et al . have demonstrated that cooking can cause significantly higher concentrations of acrolein in grocery stores . The tolerable daily intake (TDI) for acrolein has been estimated to be 7.5 μg/kg body weight .…”
Section: Introductionmentioning
confidence: 99%
“…The exogenous sources of acrolein include food, the environment, and tobacco [10]. High levels of cooking-related acrolein have been detected in grocery stores [11]. One endogenous source of acrolein is the metabolites of cyclophosphamide, a chemotherapy drug [10].…”
Section: Introductionmentioning
confidence: 99%